Cleanroom assembly of the IFMIF SRF Linac - Chambrillon Janic Kevin; Bazin Nicolas; Carin Yann; Duglué Daniel; Dzitko Hervé; Ebisawa Takashi; Gex Dominique; Jimenez-Rey David; Hasegawa Kazuo; Kondo Keitaro; Kumagai Kohki; Masuda Kai; et al. (EPJ Web of Conferences)
In complement to the development activities for fusion reactors (JT-60SA & ITER), Fusion for Energy contributes to the R&D for material characterisation facilities. Within the Broader Approach agreement, different actors from Europe to Japan collaborate to develop and assemble in Japan the LIPAC, a technical demonstrator of a D+ accelerator that will be used to produce neutron by nuclear stripping reaction on a liquid Li target. In 2024, the LIPAC is getting ready for the installation of the SRF cryomodule that will conclude its construction. Started in March 2019, the assembly was paused a first time to solve technical problems on its solenoids. Resumed in August 2022, the assembly was paused a second time after the completion of the cavity/coupler assembly to fix additional issues. In April 2024, the assembly restarted with the completion of the beam line. In this talk, we will present and details the different steps of the cleanroom assembly and how the different technical difficulties were overcome.